2012
DOI: 10.1590/s1676-06032012000300018
|View full text |Cite
|
Sign up to set email alerts
|

Serpentes do Estado de Rondônia, Brasil

Abstract: Esse estudo teve como objetivo atualizar a lista de serpentes do estado de Rondônia a partir de levantamento bibliográfico, e fornecer algumas informações sobre a distribuição das espécies. São registradas para o estado de Rondônia 118 espécies de serpentes, pertencentes a oito famílias: Leptotyphlopidae (4 espécies), Typhlopidae (1), Aniliidae (1), Boidae (6), Colubridae (21), Dipsadidae (67), Elapidae (9) e Viperidae (9). Dessas, 109 foram registradas para áreas de floresta amazônica e 27 em cerrado. A menor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
1
13
0
8
Order By: Relevance
“…As an example, the Jatapu River area-the most depauperate area when considering number of species-showed a significant contribution for the overall beta diversity pattern. These results show the importance of spatially replicated snake surveys and corroborate Neckel- Oliveira & Gordo (2004) and Bernarde et al (2012Bernarde et al ( , 2013 in showing that, although many snake species are widely distributed in the Amazonian biome, only a small proportion of the species occur-or are detected-in each locality. However, it is important to note that the high substitution of snake species in the sampled areas could be related to the broad spatial scale of our study .…”
Section: Pit Oet Oe Tcssupporting
confidence: 84%
See 1 more Smart Citation
“…As an example, the Jatapu River area-the most depauperate area when considering number of species-showed a significant contribution for the overall beta diversity pattern. These results show the importance of spatially replicated snake surveys and corroborate Neckel- Oliveira & Gordo (2004) and Bernarde et al (2012Bernarde et al ( , 2013 in showing that, although many snake species are widely distributed in the Amazonian biome, only a small proportion of the species occur-or are detected-in each locality. However, it is important to note that the high substitution of snake species in the sampled areas could be related to the broad spatial scale of our study .…”
Section: Pit Oet Oe Tcssupporting
confidence: 84%
“…For snakes, occurrence points are usually close to large urban centers (Guedes et al 2018), such as Manaus (Martins & Oliveira 1998 and Belém (Ávila-Pires 1995, Silva et al 2011. In addition, comparisons between areas become difficult due to the different methods and sampling efforts employed in each study (Magnusson et al 2005, Bernarde et al 2012, which is also an issue for snakes (Bernarde et al 2011, Guedes et al 2018. Bernarde et al (2013) observed that even though snakes have large geographic distributions in the Amazonian biome, only a small proportion of the total expected number of species occur-or are detected-at each location.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto a sua fauna de serpentes possui como principal microrregião Porto Velho, com 95 das 118 espécies com ocorrência para o Estado. Apesar da ampla distribuição dessas espécies apenas Chironius exoletus (Colubridae), é registrada para a microrregião de Alvorada do Oeste (BERNARDE et al, 2012). Sendo essa a microrregião menos amostrada quanto a espécies de serpentes.…”
Section: Introductionunclassified
“…Apesar das lacunas existentes sobre a herpetofauna no Estado, alguns estudos recentes têm demonstrado alta riqueza na região (ÁVILA-PIRES, 1995;BERNARDE & ABE, 2006;2010;BERNARDE et al, 2012), entretanto ainda há a necessidade de se conhecer melhor a diversidade desses répteis em regiões pouco estudadas, visando preencher a lacuna de informação sobre o grupo de serpentes no Estado de Rondônia.…”
Section: Introductionunclassified
“…Deste total a Amazônia abriga cerca de 150 espécies [2]. Os consideráveis valores mencionados revelam a riqueza da biodiversidade existente.…”
Section: Introductionunclassified